IDENTIFIKASI TIPE STOMATA PADA DAUN TUMBUHAN XEROFIT (Euphorbia splendens), HIDROFIT (Ipomoea aquatica), DAN MESOFIT (Hibiscus rosa-sinensis) - Raras Setyo Retno (Florea : Jurnal Biologi dan Pembelajarannya, 2015)
The aim of research to determine the type of stomata in the leaves of plants Xerophyte euphorbia (Euphorbia splendens), mesofit plant Hibiscus (Hibiscus rosasinensis), as well as hidrofit kale plant (Ipomoea aquatica). The research methods is descriptive qualitative to describe and interpret the type of stomata on the leaves. Type of stomata on the leaves of Xerophyte is anomositik. Mesofit plant hibiscus (Hibiscus rosasinensis) has a parasitic type of stomata. Hidrofit plant (Ipomoea aquatica) is anisositik, that is cells surrounded cover three neighboring cells that are not as great.